PENDEKATAN TPACK DALAM MODEL PROBLEM BASED LEARNING PADA SISWA SD KATOLIK 2 WOLOAN - Moningka, Nansi Melania; Lengkong, Jeffry S. J; Pangkey, Richard Daniel Herdi (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the implementation of the Technological Pedagogical Content Knowledge (TPACK) approach within the Problem-Based Learning (PBL) model for fifth-grade students at SD Katolik 2 Woloan. The novelty of this research lies in the contextual integration of TPACK and PBL in a primary school setting with limited technological resources—a combination that has been scarcely explored in the existing literature. The identified research gap concerns the lack of in-depth studies examining the supporting factors for implementing TPACK within PBL at the elementary level, particularly in resource-constrained areas. A qualitative research design was employed, utilizing interviews, observations, and document analysis. The findings reveal that successful integration of TPACK in PBL is supported by teacher motivation, basic school facilities, access to professional training, and active student engagement. This study contributes to the development of innovative learning practices in primary education and encourages the synergy of technology, pedagogy, and content in problem-based instructional contexts.